Organizational Communication in Implementing School Committee Role in South Tangerang City - Novianty Elizabeth Ayuna; Pudji Muljono; Djoko Susanto; Basita Gintin Sugihen (Intelektual Pustaka Media Utama, 2017)
This research aims to explore the role of communication practices of organizations in supporting the implementation of the four roles of School Committee as an advisory body, a controller, a supporter and a intermediator in an education unit. Thus research uses qualitative approach with descriptive analysis, and data collected through a focus group discussion. The result of this research shows the School Committee’s understanding of its four roles is still low; and organization communication whether between committee manager and school management and its members are still not being implemented optimally. The recommendations are spreading awareness and providing assistance to the Ministry of Education and Culture as well as the Office of Education of Tangerang Selatan on the implementation of the Law No. 44/U/2002 about the Roles and Functions of the School Committee; improving the organization communication pattern both in the internal and external environment.